Decentralization and Education in Bosnia-Herzegovina: School Autonomy, Curriculum, and Local Government Roles - Ahmad Mulalic; Ahmad Ridho (Innovative Journal of Educational Research and Insights, 2024)
This research explores the impact of decentralization on the education system in Bosnia-Herzegovina, focusing on three key areas: school autonomy, curriculum adaptation, and the role of local governments. Following the end of the conflict in 1995, the education sector underwent significant reforms aimed at addressing the diverse needs of a multi-ethnic society. Decentralization has allowed local authorities to exercise greater control over educational policies, which has led to increased school autonomy. Interviews with school principals and teachers reveal that while autonomy has enabled schools to tailor their curricula to local contexts, it has also presented challenges in maintaining educational quality. Additionally, the study highlights the varying effectiveness of local governments in supporting educational initiatives, with some regions successfully improving resources and teacher support, while others struggle with financial constraints. This research underscores the complexities of balancing local needs with national educational standards, suggesting that a more coordinated approach is necessary to enhance educational equity across all regions of Bosnia-Herzegovina.